Hepatoprotective effects of Moringa oleifera Lam (Moringaceae) leaf extracts in streptozotocin-induced diabetes in rats - Willy Tambwe Muzumbukilwa; Manimbulu Nlooto; Peter Mark Oroma Owira (Journal of Functional Foods, 2019)
Effects of methanolic leaf extracts of Moringa oleifera (MO) on hepatic injury in streptozotocin (STZ)-induced diabetes were investigated.Male Wister rats were divided into 6 groups (n = 7). Animals in group A were orally treated daily with 3.0 ml/kg/body weight (BW) of distilled water, while B, E and F were similarly treated with 500, 250 and 500 mg/kg/BW of MO, respectively. Groups C-F were rendered diabetic by single intraperitoneal injections of 45 mg/kg/BW of STZ. Additionally, group D was treated with subcutaneous insulin (2.0 U/kg/BW, bid).Diabetic animals exhibited significant weight loss, polydipsia, impaired glucose tolerance, fasting hypoinsulinemia and impaired liver function tests compared to controls. Treatment with MO methanolic leaf extracts significantly improved weight loss, polydipsia, glucose tolerance and also liver function tests in diabetic animals.MO has dose-dependent antidiabetic and hepatoprotective effects.